Cerebral venous thrombosis as a rare cause of nausea and vomiting in early pregnancy: Case series in a single referral center and literature review - Wang, Chuan; Hu, Xing; Lio, Ka U.; Lin, Jianhua; Zhang, Ning (Frontiers in Neurology, 2022)
Objectives Cerebral venous thrombosis (CVT) in early pregnancy is extremely rare and evidence limited to only a few published reports. This study aims to present our experience and summarize the available literature to further elucidate the clinical manifestations, treatment, and outcomes of CVT in early pregnancy. Methods A retrospective case series of seven patients diagnosed with CVT in early pregnancy (<12 weeks of gestations) in a tertiary referral center (2018–2021), along with a review of published literature. Results All the patients presented with nausea, vomiting, headaches, and neurological symptoms including aphasia (n = 5, 71.4%), limb weakness (n = 4, 57.1%), seizures (n = 2, 28.6%), altered mental status (n = 3, 42.9%), and blurred vision (n = 2, 28.6%). All the patients were diagnosed with CVT by neuroimaging, which revealed various extents of sinus involvement, with the transverse sinus being the most common site (n = 7, 100%) followed by the sigmoid sinus (n = 5, 71.4%). All the patients received subcutaneous low-molecular-weight heparin once the diagnosis was confirmed. Two patients with rapid deterioration underwent venous thrombectomy, and one patient subsequently underwent decompressive craniotomy but died despite the above interventions. All the other patients proceeded with induced abortion after stabilization and were discharged on oral anticoagulation for 1 year. On the 12-month follow-up, the MRI/magnetic resonance venography (MRV) revealed recanalization of sinuses and resolution of thrombi. Conclusions Cerebral venous thrombosis (CVT) in early pregnancy represents a diagnostic challenge given its rarity and nonspecific overlapping clinical features with nausea and vomiting of pregnancy/hyperemesis gravidarum (NVP/HG), which could lead to delay in diagnosis and result in rapid deterioration. Persistent or aggravating headaches combined with other focalizing neurological symptoms in NVP/HG patients could be an initial sign of CVT. Urgent MRI/MRV remains the cornerstone for diagnosis, and immediate anticoagulation is the key for disease prognosis. Glasgow coma scale (GCS) evaluation on admission is probably correlated with the prognosis. Early pregnancy combined with CVT is not a contraindication of continued pregnancy.